Perfusion MR Imaging of an Intracranial Collision Tumor Confirmed by Image-Guided Biopsy - Jun, P. (AJNR Am J Neuroradiol, 2006)
SUMMARY: We present a patient with a new intracranial mass lesion that was initially interpreted as a metastasis on conventional anatomic MR imaging. On dynamic, contrast-enhanced, susceptibility-weighted perfusion MR imaging, however, there were regional hemodynamic differences within the lesion. Image-guided open biopsy targeting these regions uncovered a collision tumor between a typical meningioma and a metastatic breast carcinoma. In cases where conventional anatomic MR imaging is ambiguous, physiology-based neuroimaging methods provide complementary physiologic information useful for discriminating between histologically unique tissue types.